Fish diversity at Cileumeuh River in District of Majenang, Cilacap Regency, Central Java [Diversitas ikan di Sungai Cileumeuh Kecamatan Majenang, Kabupaten Cilacap, Jawa Tengah] - Agus Nuryanto; Dian Bhagawati; M. Nadjmi Abulias; Indarmawan Indarmawan (Jurnal Iktiologi Indonesia, 2012)
Cileumeuh River is one of the large rivers in Western Cilacap Regency, Central Java. This river, from its upper reaches to its mouth runs through forest, farming, and housing areas. This condition leads to the prediction that the Cileumeuh River has altered its physic-chemical characteristics which led to be its being inhabited by diverse fish species. This study aims to collect data about fish species that inhabit Cileumeuh River. The survey method used was to cluster random sampling according to upper, middle, and lower parts of the river. The observed variables were number of species and abundance. During the survey a total number of 288 fish individuals were collected. Identification placed the samples into 22 species and 10 families. The obtained families were Clariidae, Loricariidae, Bagridae, Cichlidae, Synbranch-idae, Channidae, Belontiidae, Anabantidae, Cyprinidae, and Poeciliidae. Among ten families, Cyprinidae had the highest number of species (ten species) and followed by Bagridae with five species. The other eight families each have one species. High number of species and families has confirms that the Cileumeuh River has high fish diversity. Abstrak Sungai Cileumeuh merupakan salah satu sungai yang cukup besar di Kabupaten Cilacap bagian Barat. Sungai tersebut mengalir melalui areal hutan, pertanian, dan perumahan. Kondisi tersebut diduga menyebabkan perubahan fisik-kimiawi perairan yang berdampak pada beragamnya ikan yang hidup di Sungai Cileumeuh. Penelitian ini bertujuan untuk mengoleksi data mengenai spesies ikan penghuni Sungai Cileumeuh. Penelitian dilakukan menggunakan metode survei dengan teknik pengambilan sampel secara acak kelompok. Sungai dibagi menjadi tiga daerah yaitu hulu, tengah dan hilir. Variabel yang diamati adalah jumlah spesies dan jumlah individu tiap spesies. Sebanyak 288 individu ikan berhasil dikoleksi selama penelitian. Hasil identifikasi menempatkan sampel ke dalam 22 spesies dan 10 famili. Di antara kesepuluh famili yang didapatkan, famili Cyprinidae merupakan kelompok dengan jumlah spesies terbanyak yaitu 10 spesies dan diikuti oleh famili Bagridae dengan lima spesies, sedangkan delapan famili sisanya hanya memiliki satu spesies. Tingginya jumlah spesies dan famili yang diperoleh mengindikasikan bahwa Sungai Cileumeuh memiliki keragaman ikan yang tinggi.